Kajian Perkembangan Koperasi Simpan Pinjam Bina Swadaya Nusantara dan Usaha Mikro Perempuan Binaannya dengan Model ASA - Enifri, Edwin; Zakaria, Fransisca Rungkat; Sarma, Ma’mun (Universitas Brawijaya, Indonesia, 2016)
Abstract: Center for Micro Finance Development of Bina Swadaya has adopted ASA (AssociationÂ for Social Advancement) model for servicing its women microcredit beneficiaries.Â After 12 year of services, there is a presumptions that ASA model has influence towards theÂ development of saving and loan Cooperative Bina Swadaya Nusantara and also the developmentÂ of its woman microbusiness clients. The aims of this study: 1) to analyze the performanceÂ of saving and loan Cooperative Bina Swadaya Nusantara in implementing ASAÂ model, 2) to analyze the development of micro business conducting by women beneficiariesÂ of saving and loan Cooperative Bina Swadaya Nusantara, 3) to analyze the impact of ASAmodel micro credit service towards the development of microbusiness, and 4) to identifyÂ factors which influence the development of micro business using ASA model run by SavingÂ and Loan Cooperative Bina Swadaya Nusantara. The methodology of this study used correlationalÂ descriptive explanative survey with qualitative and quantitative approaches. Samplingtechnique used proportionate method by limitation of every region based on the quota,Â in accordance with a population that is in the region. This study used descriptive analysisÂ and multiple linear regression. The result shows that there has been a significant effect onÂ both saving and loan CooperativeBina Swadaya Nusantara and its women micro business.The factors which have very significant and significant effects, are: micro business's characteristicÂ and micro business services knowledge. Whereas, the Credit Officer (CO) and theÂ business environment have no significant effect.